Networked Work and Network Research: New Forms of Teamwork in the Triple Revolution. (April 2015) - Dimitrova, Dimitrina; Wellman, Barry
There has been more hype than evidence about networked work. The researchers in the two parts of this double issue issue use survey, interview, and sensor data to present systematic evidence about how networked work actually works. The first part of the issue (April) presents four articles about how professionals network. The second part of the issue (May) focuses on a particular kind of networked work—scholarly networks—including studies of how such networks change over time. Taken together, these articles show that workers tend to network with similar others. Although they integrate digital media into their work lives, they nevertheless tend to work with nearby colleagues.